2019
DOI: 10.2196/14738
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Fetal Medicine Foundation Software for Pre-Eclampsia Prediction Upon Marker Customization: Cross-Sectional Study

Abstract: BackgroundFMF2012 is an algorithm developed by the Fetal Medicine Foundation (FMF) to predict pre-eclampsia on the basis of maternal characteristics combined with biophysical and biochemical markers. Afro-Caribbean ethnicity is the second risk factor, in magnitude, found in populations tested by FMF, which was not confirmed in a Brazilian setting.ObjectiveThis study aimed to analyze the performance of pre-eclampsia prediction software by customization of maternal ethnicity.MethodsThis was a cross-sectional obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Nghiên cứu của chúng tôi cho tỷ lệ thai phụ có nguy cơ cao mắc tiền sản giật là 10,0%, tỷ lệ này tương đương với một số nghiên cứu cùng sử dụng thuật toán trên ở cả trong và ngoài nước như: ASPRE (2017) với 10,5% [5], Rezende (2019, Brazil) với 11,9% [8], Huỳnh Thị Tuyết Mai (2021, Bệnh viện Quốc Tế Thái Hòa) với 11,3% [6] và có khác biệt lớn với Trần Mạnh Linh (2020, Huế) với 21,98% [7]. Sự khác biệt trên xảy ra có thể do trong nghiên cứu của Trần Mạnh Linh có nhiều thai phụ mang yếu tố nguy cơ hơn so với nghiên cứu của chúng tôi như: tiền sử mắc tiền sản giật, tiền sử gia đình mắc tiền sản giật, tiếp xúc thuốc lá trong khi mang thai… Từ đó có thể thấy, tỷ lệ nhóm nguy cơ cao tiền sản giật được sàng lọc thông qua thuật toán của FMF là có phụ thuộc vào đặc điểm của dân số chung về các yếu tố nguy cơ tiền sản giật, nhóm dân số càng mang nhiều yếu tố nguy cơ thì sẽ cho tỷ lệ nguy cơ cao mắc tiền sản giật cao hơn.…”
Section: Kết Quả Sàng Lọc Tiền Sản Giật Theo Fmf -Kết Quả Sàng Lọc Ti...unclassified
“…Nghiên cứu của chúng tôi cho tỷ lệ thai phụ có nguy cơ cao mắc tiền sản giật là 10,0%, tỷ lệ này tương đương với một số nghiên cứu cùng sử dụng thuật toán trên ở cả trong và ngoài nước như: ASPRE (2017) với 10,5% [5], Rezende (2019, Brazil) với 11,9% [8], Huỳnh Thị Tuyết Mai (2021, Bệnh viện Quốc Tế Thái Hòa) với 11,3% [6] và có khác biệt lớn với Trần Mạnh Linh (2020, Huế) với 21,98% [7]. Sự khác biệt trên xảy ra có thể do trong nghiên cứu của Trần Mạnh Linh có nhiều thai phụ mang yếu tố nguy cơ hơn so với nghiên cứu của chúng tôi như: tiền sử mắc tiền sản giật, tiền sử gia đình mắc tiền sản giật, tiếp xúc thuốc lá trong khi mang thai… Từ đó có thể thấy, tỷ lệ nhóm nguy cơ cao tiền sản giật được sàng lọc thông qua thuật toán của FMF là có phụ thuộc vào đặc điểm của dân số chung về các yếu tố nguy cơ tiền sản giật, nhóm dân số càng mang nhiều yếu tố nguy cơ thì sẽ cho tỷ lệ nguy cơ cao mắc tiền sản giật cao hơn.…”
Section: Kết Quả Sàng Lọc Tiền Sản Giật Theo Fmf -Kết Quả Sàng Lọc Ti...unclassified
“…While other prediction models treat PE as a binary outcome, the competing risk model treats PE as an event in time, so that risk stratification can be performed at different stages of pregnancy [70][71][72]. The FMF model has undergone extensive internal and external validation in several geographically diverse cohorts [64,[73][74][75][76], with detection rates of 90% and 75% for the prediction of early and preterm preeclampsia, respectively, with a 10% false-positive rate [76]. To date, the FMF model appears to be the most well-studied [76], and external validation studies have shown comparable predictive performance corresponding to the original studies [58].…”
Section: Risk Prediction Models For Hdp/pementioning
confidence: 99%